1990
DOI: 10.1149/1.2086491
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Dependence of Intermediates in Methanol Oxidation Observed in the Steady State by FTIR Spectroscopy

Abstract: The structure of electrochemical intermediates of methanol oxidation on platinum in aqueous sulfuric acid has been investigated under steady state conditions using polarization modulation Fourier transform infrared reflection absorption spectroscopy. Terminally bonded CO and bridge‐bonded CO are observed in the cathodic to anodic sequence. However, only bridge‐bonded CO is observed in the anodic to cathodic sequence. The conventionally assumed C‒O‒H group was not observed. The spectroscopic results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…The mechanism by which such synergistic promotion of the methanol oxidation reaction is brought about has been the subject of numerous studies during the last 30 to 40 years, in which various spectroscopic methods have been employed in conjunction with electrochemistry [4±8]. A combination of cyclic voltammetry [18], in-situ ellipsometry [33], Xray absorption spectroscopy [31], on-line mass spectrometry [30] and in-situ FTIR spectroscopic studies [22,28,29], revealed that the electro-oxidation of methanol on Pt-based catalysts proceeds through the mechanism (sequence of non-elementary reaction steps) described below. First a sequence of dehydrogenation steps give rise to adsorbed methanolic residues, according to the following scheme:…”
Section: Pt Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which such synergistic promotion of the methanol oxidation reaction is brought about has been the subject of numerous studies during the last 30 to 40 years, in which various spectroscopic methods have been employed in conjunction with electrochemistry [4±8]. A combination of cyclic voltammetry [18], in-situ ellipsometry [33], Xray absorption spectroscopy [31], on-line mass spectrometry [30] and in-situ FTIR spectroscopic studies [22,28,29], revealed that the electro-oxidation of methanol on Pt-based catalysts proceeds through the mechanism (sequence of non-elementary reaction steps) described below. First a sequence of dehydrogenation steps give rise to adsorbed methanolic residues, according to the following scheme:…”
Section: Pt Electrocatalystsmentioning
confidence: 99%
“…PtOH + Pt CO À3 2Pt + CO 2 + H + + 1e ± (13) The overall oxidation process of methanol to carbon dioxide proceeds through a six electron donation process; yet, the rate determining step, derived from electrochemical steadystate measurements on Pt, through the analysis of the Tafel slope, involves a one-electron step [22]. On a pure Pt surface, the dissociative chemisorption of water on Pt is the rate determining step at potentials below % 0.7 V vs. RHE, i.e.…”
Section: Pt Electrocatalystsmentioning
confidence: 99%
“…However, an in-depth analysis of the methanol oxidation process, initially at smooth electrode surfaces, was made possible by the use of spectro-electrochemical methods. This work was carried out by several groups including those of Lamy [35], Bockris [36] and Christensen [37]. These studies essentially investigated adsorbed methanolic residues by infrared spectroscopy whereas, for the adsorbed oxygen species, ellipsometry gave appropriate results [38].…”
Section: Energy Densitymentioning
confidence: 99%
“…But the failure of Raman to achieve monolayer sensitivity, and the development of Fourier transform spectrometers led to a renewed interest in simple reflection spectroscopies. In situ IR reflectance has been applied to electrochemical interfaces by Bewick and Pons, and many others [114][115][116][117][118][119][120][121][122][123][124]. 3 In situ reflectance spectroscopy has also been performed in the visible region [125 -128], but more attention has been given to IR spectroscopy, which provides vibrational information.…”
Section: Similar Formsmentioning
confidence: 99%